2013
DOI: 10.1002/chem.201301852
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assembly of Interfacial Nanoporous Networks with Simultaneous Expression of Metal–Organic and Organic‐Bonding Motifs

Abstract: The formation of 2D surface-confined supramolecular porous networks is scientifically and technologically appealing, notably for hosting guest species and confinement phenomena. In this study, we report a scanning tunneling microscopy (STM) study of the self-assembly of a tripod molecule specifically equipped with pyridyl functional groups to steer a simultaneous expression of lateral pyridyl-pyridyl interactions and Cu-pyridyl coordination bonds. The assembly protocols yield a new class of porous open assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 64 publications
1
81
2
Order By: Relevance
“…17 Recently, the formation of complex structures formed by tripodal molecules containing pyridyl groups and Cu coordination atoms on a Ag(111) surface was observed, where both Cu-pyridyl and pyridyl-HC linkages are present. 27,56 Our result, however, is the first observation of a regular network of cavities with alternating metal-coordinated and hydrogen-bonded nodes. For NC-Ph 3 -CN on Ag(111), in case of under-stoichiometric Co deposition, the coexistence of honeycomb domains and purely organic assemblies has been reported.…”
Section: Truncated Trianglesmentioning
confidence: 57%
“…17 Recently, the formation of complex structures formed by tripodal molecules containing pyridyl groups and Cu coordination atoms on a Ag(111) surface was observed, where both Cu-pyridyl and pyridyl-HC linkages are present. 27,56 Our result, however, is the first observation of a regular network of cavities with alternating metal-coordinated and hydrogen-bonded nodes. For NC-Ph 3 -CN on Ag(111), in case of under-stoichiometric Co deposition, the coexistence of honeycomb domains and purely organic assemblies has been reported.…”
Section: Truncated Trianglesmentioning
confidence: 57%
“…[7,24] We attribute this behavior to the increased stability of the preorganized supramolecular network structure stabilized by multiple noncovalent interactions. [25] Next we explored the coordination aptitude of 2H-TPCN towards Gd atoms,w hich were also evaporated onto as ubmonolayer of 2H-TPCN held at 300 K. In marked contrast to the fivefold coordination nodes formed by dicyano-oligophenylene ligands and Ce or Gd on Ag(111), [26] an extended porous gridlike array is formed with am ononuclear squareplanar motif (Figure 2g,h). No porphyrin metalation interferes,a nd the Gd centers appear as bright round protrusions regardless of the bias polarity.Astatistical analysis of the Gd···NC distances gives ap rojected average bond length of 2.7 AE 0.5 , in agreement with recent STM observations on Gd-dicyano-oligophenylene units.…”
Section: Angewandte Zuschriftenmentioning
confidence: 99%
“…In addition, pyridyl groups can also work as ligands for the 2D MOFs. [52][53][54] Then, the lone electron pair on nitrogen atoms interacts with cationic metal atoms. Vijayaraghavan et al demonstrated that the porosities of hexagonal honeycomb networks can be tunned by depositing additional Cu atoms.…”
Section: On-surface 2d Metal-organic Frameworkmentioning
confidence: 99%
“…Vijayaraghavan et al demonstrated that the porosities of hexagonal honeycomb networks can be tunned by depositing additional Cu atoms. 53) Then, three pyridyl groups attached to the threefold symmetric aromatic molecule formed densely packed assemblies and=or porous networks by coordination with Cu adatoms, depending on the number of adatoms. This is also a typical example of intentional tuning of molecular nanoarchitectures on a surface.…”
Section: On-surface 2d Metal-organic Frameworkmentioning
confidence: 99%